Tests for the evaluation of the specific motor skills of wheelchair basketball players: A systematic review - Hadžović Miljan; Jorgić Bojan; Aleksandrović Marko; Đorđević Stefan; Kujundžić Hrvoje (University Educons, Faculty of Sports and Tourism, Novi Sad, 2022)
The foundation for the improvement of the quality of each player are their basic skills, but success in wheelchair basketball is considered to mainly depends on the level of specific motor skills which represent the end result of work done during a specific training process.The paper aims to outline the used tests for the evaluation of specific motor skills of wheelchair basketball players in papers published between 2008 and 2022. To compile the existing studies the following databases were searched:PubMed, SCIndeks, PEDro, J-GATE, SCIndes, DOAJ and Google Scholar.Research published in the period from 2008 to 2022 was analyzed. The analysis of the compiled studies to evaluate the specific motor skills of wheelchair basketball players resulted in a recommendation for the use of several tests such as the: 20m sprint with ball test, Pickup the ball test, the Lay-up test, the Pass for accuracy test, andthe Free-throw shooting test. Based on the results achieved on these tests, it is possible to perform a selection and monitor the progress of the players, as well as the impact of the applied specific training process on the development of motor skills on which success in wheelchair basketball depends.